Comparative legal analysis of the experience of creation and functioning of special economic and industrial zones of the Republic of Kazakhstan and the Republic of Uzbekistan - Akhmetov, D.M. (Bulletin of the Karaganda University “Law Series”, 2022)
The article studies the experiences of the Special Economic and Industrial Zones of the Republic of Kazakhstan and the Republic of Uzbekistan, examining the legislation on their establishment and subsequent development. Research on the different forms of incentives used in the Special Economic and Industrial Zones by these countries is conducted. As a result, a study of the experiences of the Special Economic and Industrial Zones is carried out to provide an informative and methodological basis for the development of effective approaches to the formation of zones and their implementation. A special economic zone includes a part of the territory of the Republic of Kazakhstan with clearly defined boundaries, where a special legal regime of a special economic zone prevails for conducting priority forms of activities. Special economic zones, industrial zones, and special industrial zones are established in Kazakhstan to accelerate the development of economic sectors and regions of Kazakhstan, attract all kinds of investments and create highly profitable industries, as well as cutting-edge trends. Kazakhstan’s legislation provides for uniform requirements and provisions for domestic and foreign companies to present the status of a participant in the Special Economic and Industrial Zones and to determine tax and customs exemptions. According to Paragraph 1 of Article 201 of the Customs Code, the customs regulations of a free customs zone constitute the customs procedure applicable to foreign goods and goods of the Union, under which such goods are traded within the territory of the Special Economic and Industrial Zone or its part without payment of customs duties, taxes, specially assessed duties upon conditions of placing these goods under this customs procedure and their application according to such a customs procedure